A facile synthesis of ruthenium/reduced graphene oxide nanocomposite for effective electrochemical applications. (October 2019) - Dao, Van-Duong; Hoa, Nguyen Duc; Vu, Ngoc Hung; Quang, Dang Viet; Hieu, Nguyen Van; Dung, Tran Thi Ngoc; Viet, Nguyen Xuan; Hung, Chu Manh; Choi, Ho-Suk
Graphical abstract: Highlights: A facile liquid plasma is introduced to synthesize Ru/RGO nanocomposites. Ru nanocrystals are homogeneously distributed on the RGO surface. The Ru/RGO nanocomposites processed high capacitance of 136.7 F·g −1 . Dye-sensitized solar cells fabricated with Ru/RGO shows 6.78% efficiency. Abstract: The synthesis of advanced functional nanomaterials for electrochemical applications, such as water splitting, dye-sensitized solar cells (DSCs), and supercapacitor has been the topic of interest in recent years. This work presents the synthesis of ruthenium (Ru)/reduced graphene oxide (RGO) nanocomposite by using a facile and scalable liquid plasma-assisted method and its application as an electrode material in electrochemical applications for supercapacitor and triiodide reduction at counter electrodes (CEs) of DSCs. As the results, Ru nanoparticles have a size in the range of 4–10 nm that were homogenously distributed on the surface of the RGO layer. Electrochemical measurements demonstrated that the synthesized material is suitable for supercapacitor applications, whereas the capacitance is approximately 136.7 F·g −1 at a scan rate of 20 mV·s −1 . The developed materials are applied in CEs of DSCs. We found that the efficiency of 6.78% for DSCs with CE fabricated by Ru/RGO which is higher than that of 6.20% for a cell assembled with Pt electrode.